The Effects of Occupational Stress on Personnel's Quality of Life and Desire to Continue Serving in Emergency Operation Center - Tahere Sharifi; Razieh Sepehrian; Mina Namdari (Kerman University of Medical Sciences, 2016)
Introduction: The Emergency Operation Center (EOC) is a prehospital community-based health management system that its main capital are its employees. However, occupational stress in personnel have negative effect on their quality of life and can lead to leaving the occupation. The aim of this study was to evaluate occupational stress and its effect on quality of life and desire to continue serving in personnel of Emergency Operation Center in Kerman. Methods: In this descriptive-analytical study, 200 personnel of Emergency Operation Center in Kerman in 2013 were included using stratified sampling method. The data was gathered using questionnaires HSE and WHOQOL BREF and analyzed by using chi-square test, Pearson correlation coefficient, and linear regression. Results: The results show that level of occupational stress in 49.3% of personnel was moderate and the quality of life in 52.9% of them was high. It was also found that the score of desire to continue serving in personnel was 4.15%. Therefore, there was reverse relationship between quality of life and occupational stress but direct relationship between quality of life and desire to continue serving in Emergency Operation Center. Conclusion: The results of this study showed that reducing occupational stress can increase the personnel's quality of life and consequently the desire to continue serving in Emergency Operation Center. The main stressors in personnel is how administrators support them and make changes in the organization; therefore, it is recommended to managers to more support the personnel for reducing stress in them. Keywords: Occupational Stress, Quality of Life, Desire to Continue Serving, Emergency Operation Center Citation: Sharifi T, Sepehrian R, Namdari M. The Effects of Occupational Stress on Personnel's Quality of Life and Desire to Continue Serving in Emergency Operation Center. Journal of Health Based Research 2016; 2(1): 93-104.